2019
DOI: 10.1302/0301-620x.101b11.bjj-2019-0196.r1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-loaded bone cement is associated with a lower risk of revision following primary cemented total knee arthroplasty

Abstract: Aims Antibiotic-loaded bone cements (ALBCs) may offer early protection against the formation of bacterial biofilm after joint arthroplasty. Use in hip arthroplasty is widely accepted, but there is a lack of evidence in total knee arthroplasty (TKA). The objective of this study was to evaluate the use of ALBC in a large population of TKA patients. Materials and Methods Data from the National Joint Registry (NJR) of England and Wales were obtained for all primary cemented TKAs between March 2003 and July 2016. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 57 publications
0
28
1
2
Order By: Relevance
“…Previous studies have indicated that local use of ALBC is effective in preventing both PJI [14][15][16][17] and FRI [18][19][20][21] following joint arthroplasty and open fracture surgery, respectively. After analyzing the prophylactic effect of ALBC against infection in primary cemented TKA of 731,214 cases, Jameson et al 16 concluded that ALBC was associated with a lower risk of revisions for infections (hazard ratio 0.84, 95% CI 0.67-1.01). As for FRI, a recent systematic review 22 summarized the effect of local antibiotic prophylaxis when treating open limb fractures.…”
mentioning
confidence: 99%
“…Previous studies have indicated that local use of ALBC is effective in preventing both PJI [14][15][16][17] and FRI [18][19][20][21] following joint arthroplasty and open fracture surgery, respectively. After analyzing the prophylactic effect of ALBC against infection in primary cemented TKA of 731,214 cases, Jameson et al 16 concluded that ALBC was associated with a lower risk of revisions for infections (hazard ratio 0.84, 95% CI 0.67-1.01). As for FRI, a recent systematic review 22 summarized the effect of local antibiotic prophylaxis when treating open limb fractures.…”
mentioning
confidence: 99%
“…With an estimated annual cost of US $8659 per patient, diabetes foot care poses an increasing socioeconomic burden for the public health [49]. The cost-effectiveness analyses of ALBC have mostly been done in the knee, hip, and shoulder arthroplasty studies [50][51][52][53][54]. Moreover, in order to achieve the standardization of ALBC use, these studies have investigated factors such as cement/antibiotic mix models [50], quantity of antibiotics loaded [50,51], and nature of bone cement [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data it was concluded that 8.7 revisions per 1000 TKRs could be avoided at 10 years, if ALBC is used for all primary TKA. 12 The results from a recently conducted quasi-randomized clinical trial with 848 intracapsular neck fracture patients in the UK have added further evidence to which extent a high dose double antibiotic-loaded bone cement is able to reduce the infection risk in high risk patients. If the bone cement Copal G+C (Hereaus Medical, Yardley, PA, USA) (high dose antibiotic content: 1 g gentamicin and 1 g of clindamycin in 40 g of cement powder) was used for cemented hemi-arthroplasty instead of the low dose cement PALACOS R+G (low dose antibiotic cement: 0.5 gentamicin in 40 g of cement powder), the incidence rate of superficial and deep infections was drastically reduced from 5.3% to 1.7%.…”
Section: National Joint Registry Of England Wales and Northern Irelandmentioning
confidence: 99%